2016
DOI: 10.1007/s10995-016-2126-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-eclampsia in American Indians/Alaska Natives and Whites: The Significance of Body Mass Index

Abstract: Introduction The prevalence of pre-eclampsia, a major cause of maternal morbidity, varies by race, being greater in African Americans, and lower in Asians and Hispanics than in White women. Little is known about its prevalence in American Indians/Alaska Natives (AI/ANs). We estimated pre-eclampsia risk in AI/ANs compared to Whites, with consideration of the potential effect of obesity, a major risk factor for pre-eclampsia, and a condition disproportionately affecting AI/AN women. Methods This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
1
23
1
Order By: Relevance
“…Assessments performed in other contexts have already shown that Native American women and those native to Alaska have a higher risk of preeclampsia than white women, and this effect is also modulated by body mass index (BMI). 17 In general, the results of the current study diverge from other studies in the literature that were related to the subject. In the United Kingdom, a case-control study demonstrated that black African women had twice the chance of having an MNM event in comparison to white Europeans.…”
Section: Discussioncontrasting
confidence: 99%
“…Assessments performed in other contexts have already shown that Native American women and those native to Alaska have a higher risk of preeclampsia than white women, and this effect is also modulated by body mass index (BMI). 17 In general, the results of the current study diverge from other studies in the literature that were related to the subject. In the United Kingdom, a case-control study demonstrated that black African women had twice the chance of having an MNM event in comparison to white Europeans.…”
Section: Discussioncontrasting
confidence: 99%
“…study. [ 13 ] In addition, 15% of preeclamptic patients were smokers which in turn may affect the occurrence of PE; since smoking reduces the risk of PE. In addition, nonsmokers both before and during pregnancy have a superior risk of PE compared to smoker patients.…”
Section: Discussionmentioning
confidence: 99%
“…AI/AN women in Washington State had a 17% increased risk of preeclampsia compared to white women, even after adjusting for age, socioeconomic status, and smoking. 19 Obesity was a confounder, highlighting an important risk factor for pregnancy-related morbidity and mortality. 19 Hypertensive disorders first diagnosed during pregnancy were also higher for AI/AN than white women (12.8% and 6.7%, respectively, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%